The Influence of STEM Learning Approach on Mathematical Literacy Skills - Abdullah Abdullah; Isnarto Isnarto; Scolastika Mariani; Isnaini Rosyida (EduMa: Mathematics education learning and teaching, 2025)
Mathematical literacy is an essential competency that students need to develop in the twenty-first century. However, the 2022 Programme for International Student Assessment (PISA) results indicate that Indonesian students continue to demonstrate relatively low levels of mathematical literacy. Therefore, effective instructional innovations are required to improve this competency, one of which is the Science, Technology, Engineering, and Mathematics (STEM) learning approach. This study aimed to examine the effectiveness of the STEM learning approach in improving students' mathematical literacy through a meta-analysis. Three relevant empirical studies were analyzed. The findings revealed that two studies produced high effect sizes, while one study produced a moderate effect size. The combined effect size was 1.220507, indicating a high overall effect of the STEM learning approach on students' mathematical literacy. Furthermore, the t-test results showed a statistically significant difference between students' pretest and posttest scores. The mean pretest score was 30.15, whereas the mean posttest score increased to 62.59. These findings demonstrate that the STEM learning approach has a significant positive effect on improving students' mathematical literacy.